2022
DOI: 10.1038/s41598-022-05452-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antimicrobial susceptibility pattern of urinary tract infection among pregnant women attending Hargeisa Group Hospital, Hargeisa, Somaliland

Abstract: The aim of this study was to determine the prevalence, antimicrobial susceptibility pattern and associated factors of urinary tract infection (UTI) among pregnant women attending Hargeisa Group Hospital (HGH), Hargeisa, Somaliland. A cross-sectional study was conducted at HGH, Hargeisa, Somaliland and participants were selected by systematic random sampling technique. Clean catch midstream urine samples were collected from 422 participants and cultured and antimicrobial susceptibility pattern was determined fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
6
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 46 publications
3
6
1
2
Order By: Relevance
“…The present study includes the sensitivity patterns of E. coli isolates from the ASB cases against 11 different antimicrobial classes as per institutional antibiotic guidelines in the study setting and National Antibiotics Guideline (Malaysia) 2019 [77]. The result from this study was in agreement with previous reports which have shown that resistance to ampicillin was the highest in E. coli isolated from ASB [78]. The occurrence of resistance to CRO and CTX in this study is comparatively lower than the 100% resistance reported for these antibiotics in Cameroon [79].…”
Section: Antibiotic Resistancesupporting
confidence: 88%
See 1 more Smart Citation
“…The present study includes the sensitivity patterns of E. coli isolates from the ASB cases against 11 different antimicrobial classes as per institutional antibiotic guidelines in the study setting and National Antibiotics Guideline (Malaysia) 2019 [77]. The result from this study was in agreement with previous reports which have shown that resistance to ampicillin was the highest in E. coli isolated from ASB [78]. The occurrence of resistance to CRO and CTX in this study is comparatively lower than the 100% resistance reported for these antibiotics in Cameroon [79].…”
Section: Antibiotic Resistancesupporting
confidence: 88%
“…The occurrence of resistance to CRO and CTX in this study is comparatively lower than the 100% resistance reported for these antibiotics in Cameroon [79]. The resistance to trimethoprim-sulfamethoxazole in this study is also lower than 60% reported in Somaliland [78]. According to the European Association of Urology guidelines, an agent should be considered for empiric treatment of uropathogenic bacteria if the resistance is less than 20% [80].…”
Section: Antibiotic Resistancecontrasting
confidence: 55%
“…Samples 55 were positive for bacterial culture, and by (28.06% ) (Figure 1) and included the age (less than one year), with 12 females (41.37%) and males 17 (58.62%) and the age (1--5) year, the females was 12 (70.85%) and males 5 (29.41%), the age (6-10) year and (11)(12)(13)(14)(15) year the number of females with UTI was 8 (100%) and 1 (100%) as shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…were (19.1, 14.3, 11.9, 11.9, 9.5, 9.5, 4.8, 4.8)% respectively. 12 Noted in his study that the prevalence of bacteria isolated from urine was E. coli, Coagulase negative Staphylococcus (CoNS), S. aureus, K. pneumonia, P. aeruginosa, Proteus mirabilis, Citrobacter spp. and M. morganii at a percentage 43.5, 16, 16, 8.7, 7.2, 5.8, 4.4, 1.5%, respectively 13 noted the prevalence of K. pneumoniae from urine.…”
Section: Resultsmentioning
confidence: 99%
“…Stasis urine dan kerusakan mekanisme refluks fisiologis menimbulkan kondisi yang mendukung pertumbuhan bakteri dan infeksi ascending (Werter et al, 2021;Azami et al, 2019;Lee et al, 2019;Yan et al, 2018). Jika infeksi ini tidak diobati, dapat menyebabkan janin lahir dengan berat badan lahir rendah, retardasi pertumbuhan intrauterin, persalinan prematur dan bayi prematur, kematian janin intrauterin, dan peningkatan mortalitas dan morbiditas prenatal serta komplikasi ibu termasuk anemia, preeklamsia, gagal ginjal, septikemia, dan sindrom pernapasan dewasa (Ali et al, 2022).…”
unclassified